Validação do questionário Baecke modificado para idosos e proposta de valores normativos - Ueno, Deisy Terumi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The assessment of the level of physical activity in the elderly has extremely relevant because it allows the development and implementation of interventions in order to minimize and control problems related to the low level of physical activity and functional decline in health. The measurement through questionnaires is an appropriate method to evaluate large populations, as well as having a relatively low cost and require little time for administration. Since a questionnaire adapted for the elderly differs in some respect to validity studies, the aim of this study was to estimate the validity of the Modified Baecke Questionnaire for Older Adults (MBQOA) through accelerometer in elderly women. To select the sample, we used the technique of random sampling and stratified conglomerate, and the final sample comprised 100 women of Rio Claro/SP, aged between 60 and 70 years, selected from among 100 randomly selected census tracts for the study. The elderly should have sufficient cognitive skills as assessed by the Mini Mental State Examination. After they answered a questionnaire characterization, the MBQOA and economic classification . All elderly should also use an accelerometer for 7 days. Data were analyzed using descriptive analysis. It is the normality of the data using the Kolmogorov - Smirnov test, which showed non- parametric data. Thus, we used the Spearman correlation test to assess the association between the accelerometer and the QBMI, and linear regression to assess the level of agreement. It was established cutoff points for tertiles for classification as low, moderate and high levels of physical activity (LPA). The level of significance was set at p ≤ 0.05 for all analyzes. There was a moderate correlation between the total score of the QBMI and total physical activity accelerometer (rho = 0.42). The cutoff points were defined: ≤ 9.11 points down LPA, between 9,12 and 16,17 for moderate LPA and LPA to high ≥ 16.18. It was...

A avaliação do nível de atividade física em idosos possui extrema importância, pois permite a elaboração e implementação de intervenções com o intuito de minimizar e controlar problemas relacionados ao baixo nível de atividade física e ao declínio funcional na saúde. A mensuração por meio de questionários é um método adequado para avaliar grandes populações, além de possuir um custo relativamente baixo e demandar de pouco tempo para administração. Visto que um questionário adaptado para idosos apresenta algumas divergências em relação aos estudos de validade, o objetivo do presente estudo foi estimar a validade do Questionário Baecke Modificado para Idosos por meio do acelerômetro em idosas. Para a seleção da amostra utilizou-se a técnica de amostragem aleatória e estratificada por conglomerado, sendo a amostra final composta por 100 mulheres do município de Rio Claro/SP, com idade entre 60 e 70 anos, selecionadas dentre os 100 setores censitários sorteados para o estudo. As idosas deveriam possuir capacidade cognitiva preservada, avaliada pelo Mini Exame do Estado Mental (MEEM). Após, elas responderam a um questionário de caracterização, ao QBMI e um de classificação econômica. Todas as idosas também deveriam utilizar um acelerômetro por 7 dias. Os dados foram analisados por meio de análise descritiva. Verificou-se a normalidade dos dados por meio do teste de Kolmogorov-Smirnov, o qual apontou natureza não-paramétrica dos dados. Assim, utilizou-se o teste de correlação de Spearman para verificar a associação entre o acelerômetro e o QBMI, e o teste de regressão linear para avaliar o nível de concordância. Estabeleceu-se os pontos de corte pelos tercis para classificação em baixo, moderado e alto nível de atividade física (NAF). O nível de significância adotado foi de p≤0,05 para todas as análises. Houve correlação moderada entre o score total do QBMI e atividade física total do...
Keywords: Physical education and training; Educação fisica; Questionarios; Estudos de validação; Aptidão física; Exercícios físicos para idosos; Rio Claro (SP)